Brain Mapping : Indications and Techniques. - Quinones-Hinojosa, Alfredo (Thieme Medical Publishers, Incorporated, 2019)
Comprehensive resource features state-of-the-art brain mapping techniques and pearls from international recognized neurosurgeons Alfredo Quinones-Hinojosa and Kaisorn Chaichana and coeditor Deependra Mahato Despite advances in imaging techniques to identify eloquent cortical brain regions and subcortical white matter, brain mapping is the only method for obtaining real-time information with high sensitivity and specificity. This groundbreaking technology greatly enhances the neurosurgeon's ability to safely resect challenging lesions located in eloquent areas of the brain. Brain Mapping: Indic.